2021
DOI: 10.46367/jps.v2i2.381
|View full text |Cite
|
Sign up to set email alerts
|

Financial Distress Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia

Abstract: Companies engaged in the food and beverage business have a very high chance of success in running their business, given the increasingly high level of food and beverage consumption for the community. Information based on financial ratios needs to be improved in other forms of financial analysis to ascertain the future risk level. The purpose of this study is to analyze financial distress for food and beverage sub-sector companies listed on conventional stocks and Islamic stocks on the Indonesia Stock Exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
10

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 2 publications
0
6
0
10
Order By: Relevance
“…PT Ramayana Lestari Sentosa Tbk menutup 19 toko Ramayana pada tahun 2021. Pandemic covid-19 menjadi pemicu pembatasan operasional pada berbagai pusat perbelanjaan sehingga menimbulkan turunnya minat beli oleh masyarakat sekitar [3]. Lalu PT.…”
Section: Pendahuluanunclassified
“…PT Ramayana Lestari Sentosa Tbk menutup 19 toko Ramayana pada tahun 2021. Pandemic covid-19 menjadi pemicu pembatasan operasional pada berbagai pusat perbelanjaan sehingga menimbulkan turunnya minat beli oleh masyarakat sekitar [3]. Lalu PT.…”
Section: Pendahuluanunclassified
“…Financial performance can also be interpreted as the company's financial performance, which can be seen in how the company survives and the company's ability to generate profits. This performance can be measured using ratios such as Profitability and Leverage [8].…”
Section: Financial Performancementioning
confidence: 99%
“…Profitability is the ability of a company to generate earnings through its investments by company management with certain policies. One profitability measurement uses the Return On Assets (ROA) ratio [8], [9]. ROA is a measurement used to find out how well the company's assets are used to generate profits.…”
Section: Profitabilitymentioning
confidence: 99%
“…Additionally, according to Hutauruk et al (2021) companies with high liquidity ratios are less likely to face bankruptcy threats because good liquidity indicates that the company is financially capable of fulfilling its short-term debts. However, Fitri & Syamwil (2020) found that liquidity does not have an impact on a company's financial distress condition.…”
Section: Hypotheses Relationship Liquidity On Financial Distressmentioning
confidence: 99%